2006
DOI: 10.1590/s0104-66322006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of water removal from water/ethanol mixtures using supercritical carbon dioxide

Abstract: -Techniques involving supercritical carbon dioxide have been successfully used for the formation of drug particles with controlled size distributions. However, these processes show some limitations, particularly in processing aqueous solutions. A diagram walking algorithm based on available experimental data was developed to evaluate the effect of ethanol on the efficiency of water removal processes under different process conditions. Ethanol feeding was the key parameter resulting in a tenfold increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…This is because the CO 2 /water parameters from eq 13 give a very good description of the water content in the vapor phase at low ethanol concentration of the liquid phase, as Figure 10 shows. Table 7 also shows that the calculated results from an empirical method 13 fit well the data; yet, in most cases, it slightly underestimates the CO 2 consumptions.…”
Section: Water Removalmentioning
confidence: 74%
See 2 more Smart Citations
“…This is because the CO 2 /water parameters from eq 13 give a very good description of the water content in the vapor phase at low ethanol concentration of the liquid phase, as Figure 10 shows. Table 7 also shows that the calculated results from an empirical method 13 fit well the data; yet, in most cases, it slightly underestimates the CO 2 consumptions.…”
Section: Water Removalmentioning
confidence: 74%
“…Calculation Method. A step-by-step procedure 13 and the PRSV-EoS were used to calculate the relevant quantities in the experimental process described above. The first step was to determine the initial working point at the system's pressure (10.0 MPa) and temperature (313.2 K) from the initial feed of the aqueous ethanol a Binary interaction parameters obtained using the alternative objective function, AAD ) AADx ) Here n in should be small enough to keep the results steadily unchanged; our calculations showed that 1% or less of the initial CO 2 mole number was a convenient choice (experiment also required that CO 2 flow rates should be small enough, here 3-7 g min -1 that was small compared to the total CO 2 consumed).…”
Section: Water Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The former represents a new generation of membrane separation process involving a phase change to form a gaseous permeate and liquid retentate using a semipermeable membrane, whereas the latter employs molecular sieves or biomaterials (e.g., corn grits, cassava starch) to selectively adsorb water. Another process for dehydrating ethanol is supercritical fluid extraction, in which carbon dioxide is employed as the solvent. Liquid CO 2 is used to extract the ethanol, and then CO 2 is flashed off by depressurization to recover anhydrous ethanol . However, regardless of whether they are distillation or nondistillation technologies, all of the above processes involve either considerable energy consumption or huge capital investments because of their complex process configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of O/W emulsions in the place of solvent requires a process setup in order to improve water solubility in SC-CO 2 . For instance, the water removal efficiency can be raised by increasing the pressure and temperature [47].…”
Section: Technologies For β-Carotene Encapsulation In Dried Systemsmentioning
confidence: 99%